2020
DOI: 10.1021/acs.joc.0c02473
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anion-Binding Schreiner’s Thiourea on DMAP Salts: Synergistic Catalysis toward the Stereoselective Dehydrative Glycosylation from 2-Deoxyhemiacetals

Abstract: Amines are used as additives to facilitate or increase the host−guest chemistry between the thiourea and the anions of Bronsted acids. However, we here demonstrate, for the first time, the synergistic effect of the combination of DMAP/HCl/ Schreiner's thiourea in catalyzing dehydrative glycosylation. The variations in the electronic effects of the cationic Bronsted acid part (the protonated DMAP) in the presence of chloride binding Schreiner's thiourea have been discussed using NMR and X-ray crystallographic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…NMR analysis has previously been used to provide evidence for H-bonding interactions between thiourea catalysts and substrates. 59–61 We noted that the solubility of catalyst 1 in CDCl 3 was increased dramatically in the presence of diethyl vinylphosphonate which is consistent with formation of an H-bonded complex between the two species. H-Bonding interactions between thioureas and phosphoryl compounds have been studied using 31 P NMR and used to create a scale of catalyst H-bonding ability.…”
Section: Resultsmentioning
confidence: 61%
“…NMR analysis has previously been used to provide evidence for H-bonding interactions between thiourea catalysts and substrates. 59–61 We noted that the solubility of catalyst 1 in CDCl 3 was increased dramatically in the presence of diethyl vinylphosphonate which is consistent with formation of an H-bonded complex between the two species. H-Bonding interactions between thioureas and phosphoryl compounds have been studied using 31 P NMR and used to create a scale of catalyst H-bonding ability.…”
Section: Resultsmentioning
confidence: 61%
“…N , N ′−Bis [3,5−bis(trifluoromethyl)phenyl]−thiourea (Schreiner’s thiourea catalyst). The title compound was prepared according to a modified literature procedure [ 139 ]. A 4 mL-GC vial was charged with 3,5-bis(trifluoromethyl)aniline (573 mg, 2.50 mmol, 1.00 equiv.)…”
Section: Methodsmentioning
confidence: 99%
“…Very recently Kancharala et al have reported the influence of anion-binding thiourea ( 12 ) on 4-dimethylaminopyridine salts toward α-selective synthesis of 2-deoxyglycosides ( 124 ) from their corresponding hemiacetals ( Ghosh et al, 2021 ). Combination of Schreiner’s thiourea ( 12 ), DMAP and HCl was used for dehydrative glycosylation of hemiacetals ( 130 ) in 1,2-dichloroethane solvent at 40°C (IV in Scheme 11 ).…”
Section: Techniques For 12- Cis Glycosylation Reac...mentioning
confidence: 99%